Architectural Exploration of Art Concepts - Galvin, Vanessa (Common Ground Publishing, 2011)
This study argues for a communal sphere or common ground that enables the interplay of methods and techniques generally accepted as belonging to either the pictorial arts or architecture to be considered within the same exploratory context, resulting in images that belie their origin and are suggestive of both ambiguity and alliance. Driven by the apparent limitations of these resultant images, a further phenomenal outcome of this relationship is discussed: that is, the way in which the expression of these shared ideas is enhanced via their elevation from the pictorial plane into authentic and innovative architectural syntheses of the same artistic ideals.